Droplet-based combinatorial assay for cell cytotoxicity and cytokine release evaluation - Antona, Silvia; Abele, Tobias; Jahnke, Kevin; Dreher, Yannik; Göpfrich, Kerstin; Platzman, Ilia; Spatz, Joachim P. (Advanced functional materials, 2020)
Balancing the maximal efficacy of interferon gamma (IFN-ɣ)-based therapies with its side effects is a great challenge for future cytokine treatments. To achieve this, the development of single-cell technologies that study IFN-ɣ release in correlation with antitumor activity would represent a huge step forward. To this end, droplet-based microfluidics is employed to quantitatively investigate IFN-ɣ secretion from single natural killer (NK) cells in correlation with their cytotoxic activity against a specific target. The method relies on co-encapsulation of NK-92 cells, target cancer cells, polystyrene beads conjugated with specific IFN-ɣ capture antibodies, and fluorescently labeled detection antibodies inside water-in-oil compartments. The secreted cytokines are captured and detected by localized fluorescence at the periphery of the beads. NK-92's cytotoxicity is evaluated simultaneously by means of a fluorescent DNA intercalating agent, which penetrates the membranes of dead target cells. To deepen the understanding of the role of the cytokine in antitumor immunomodulation, the impact of different doses of human recombinant IFN-ɣ on the cytolytic activity of NK-92 cells shows a trend that the higher the dose the lower the cytolytic activity of NK cells. The developed method represents a simple quantitative approach to unravel the complex heterogeneity of NK cells toward IFN-ɣ secretion and cytolytic activity.